Strategi Sekolah Dalam Pembentukan Karakter (Religius, Disiplin, Dan Toleransi) Siswa MIN 2 Mojokerto - Fatakhul Khoir Mujiyo; Ika Agustin Adityawati (IAI Al Khoziny Buduran Sidoarjo, 2022)
Character is an indication of how a nation traces and transcends a period and begins to a higher degree. A great nation is a nation that is able to create a society that is able to compete and influence world civilization. The character of each person is not formed spontaneously but takes a long time with a systematic process. Education in Indonesia now prioritizes the formation of student character. This is done to cultivate good and excellent karate students. The purpose of this research is to find out how the school's strategy in shaping the character of students in MIN 2 Mojokerto and what are the inhibiting factors and solutions in shaping the character of students at MIN 2 Mojokerto. The method used in this research is a qualitative method. The research was conducted at MIN 2 Mojokerto and the subjects in this study were the principal, the head of the curriculum, the head of student affairs, the BK teacher, and the fifth grade teacher. After the research was conducted, the results showed that the strategy used was in the form of habituation of religious activities in schools such as obligatory prayers and sunnah prayers. , reading Asmaul Husna, religious extracurricular. While the obstacles experienced are students who are closed, selfish, and have a low economy and provide explanations and directions and facilitate students.